Hofstede’s Cultural Dimensions (Masculinity Vs. Femininity) And Its Impact On Earnings Management - SATAM S., Hussein; WISAM N., Hussein; ALI I., Hussein (Opción, 2019)
Hofstede’s cultural dimensions (Power Distance, Individualism, Uncertainty Avoidance, Masculinity, Long term orientation and Indulgence) play an important role in social sciences, Gray used four dimensions in the field of accounting and completed his mission by Borker, the study aims to know the extent of the cultural dimensions in the Iraqi environment, as well as to test the extent of the impact of gender as a cultural dimension on the management of accounting Earnings Man- agement in a sample of companies listed in the Iraqi stock exchange.